Mass spectrometry analysis of dried cervico-vaginal fluid on paper cards in relation to ovarian cancer. - Lindberg, Julia Hedlund; Widgren, Anna; Ivansson, Emma; Gustavsson, Inger; Stålberg, Karin; Gyllensten, Ulf; Bergquist, Jonas; Enroth, Stefan (Uppsala University, 2024)
A total of 160 samples (all women; 40 health controls, 120 with malign or benign diagnosis after suspicion of ovarian cancer collected at time of diagnose (N=104) or before (N=16)) with dried cervicovaginal fluid (CVF) on paper cards (FTA elute micro card) were included in the study. The CVF-sampels were collected with a sampling brush (Viba brush) that was inserted and rotated in the top of the vagina, vaginal fornices, and portio but not in the cervical canal. The brush was then applied to the coloured area of the FTA elute micro card and rotated one circle, left to dry five minutes before closure and stored in room temperature.

Mass-spectrometry measurements for the controls (N=40) and a subset of the cases in the second sample set (N=20) have been carried out previously by the Mass Spectrometry facility at the Biomedical Centre, Uppsala, Sweden. The data from the controls were previously published in Gutiérrez et al (Cancers 2021, Vol. 13, Page 2592). Here, the remainder of the second sample set (N=84) and the 16 samples collected before diagnosis were analysed at the same facility as used previously. The sample processing and LC-MS/MS measurements were carried out here exactly as described in Gutiérrez et al (Cancers 2021, Vol. 13, Page 2592), except for an update to the version of the UniProt database used in the final annotation of the proteins. In brief, one 3.5 mm punch was extracted from each sample. The proteins were reduced, alkylated and on-filter digested by trypsin according to a standard operating procedure. The collected peptide filtrate was vacuum centrifuged to dryness using a speedvac system. Dried peptides were resolved in 60 μL of 0.1% FA and further diluted 5 times prior to nano- LC-MS/MS. The peptides were separated in reversed-phase on a C18-column with 90 min gradient and electrosprayed on-line to a Q Exactive Plus mass spectrometer (Thermo Finnigan). Tandem mass spectrometry was performed applying Higher-energy C-trap Dissociation (HCD). The acquired data (RAW files) were processed using MaxQuant software, version 1.5.1.2, and database searches were performed using the implemented Andromeda search engine (Urgen Cox, J. et al. J. Proteome Res 10, 2011). MS/MS spectra were correlated to a FASTA database containing proteins from Homo sapiens extracted from the UniProt database (release date: May 2021). A decoy search database, including common contaminants and a reverse database, was used to estimate the identification false discovery rate where a rate of 1% was accepted. The search parameters included: maximum 10 ppm and 0.6 Da error tolerances for the survey scan and MS/MS analysis, respectively; enzyme specificity was trypsin; maximum one missed cleavage site allowed; cysteine carbamidomethylation was set as static modification; and oxidation of methionine was set as variable modification. The search criteria for protein identification were set to at least two matching peptides of 95% confidence level per protein.

The study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Regional Ethics Committee in Uppsala, Sweden (Dnr 2012/099) and Göteborg (Dnr: 201-15).
Keywords: Proteomics and metabolomics; Cancer diagnosis; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi